2017
DOI: 10.1021/acs.jproteome.7b00188
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Amyloid Corneal Aggregates from TGFBI-H626R Lattice Corneal Dystrophy Patient Implicates Serine-Protease HTRA1 in Mutation-Specific Pathogenesis of TGFBIp

Abstract: TGFBI-associated corneal dystrophies are inherited disorders caused by TGFBI gene variants that promote deposition of mutant protein (TGFBIp) as insoluble aggregates in the cornea. Depending on the type and position of amino acid substitution, the aggregates may be amyloid fibrillar, amorphous globular or both, but the molecular mechanisms that drive these different patterns of aggregation are not fully understood. In the current study, we report the protein composition of amyloid corneal aggregates from latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 62 publications
1
19
0
Order By: Relevance
“…The protein composition of the aggregates was compared with healthy control tissue to identify the accumulating proteins. This approach has been applied in subsequent studies by ourselves and others that determined the protein aggregate compositions related to TGFBI-linked corneal dystrophies (Courtney et al, 2015;Karring et al, 2013;Poulsen et al, 2016;Poulsen et al, 2014b;Venkatraman et al, 2017).…”
Section: Protein Profiles Of Gcd Depositsmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein composition of the aggregates was compared with healthy control tissue to identify the accumulating proteins. This approach has been applied in subsequent studies by ourselves and others that determined the protein aggregate compositions related to TGFBI-linked corneal dystrophies (Courtney et al, 2015;Karring et al, 2013;Poulsen et al, 2016;Poulsen et al, 2014b;Venkatraman et al, 2017).…”
Section: Protein Profiles Of Gcd Depositsmentioning
confidence: 99%
“…The protein profiles of amyloid LCD deposits from patients carrying R124C, A546D, A546D/P551Q, V624M, or H626R TGFBIp mutations show the accumulation of other amyloidogenic proteins in addition to TGFBIp, as well as nonfibrillar amyloid-associated proteins. The amyloidogenic proteins include apolipoprotein A-I, apolipoprotein A-IV, lysozyme C, protein S100-A8, protein S100-A9, and lactotransferrin (Courtney et al, 2015;Karring et al, 2013;Karring et al, 2012;Poulsen et al, 2014b;Venkatraman et al, 2017). Whether the amyloidogenic proteins are directly involved in the progression of amyloid deposits or merely innocent coaggregating bystanders is not known.…”
Section: Protein Profiles Of Lcd Depositsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several studies that have investigated and reported the protein composition of corneal aggregates from dystrophic patients with different TGFBI mutations . Our group has reported the protein composition of corneal aggregates from lattice corneal dystrophy (LCD) patients with H626R and R124C mutations using liquid chromatography‐mass spectrometry/mass spectrometry (LC‐MS/MS) methods . All studies have identified several amyloidogenic, non‐amyloid fibrillar proteins and TGFBIp to be the major components of the corneal aggregates and suggested the possibility of differences in proteolytic procession of mutant protein compared to wild type (WT) …”
mentioning
confidence: 99%
“…It has been reported that the peptides derived from the 1 st and 4 th FAS-1 domains of mutant TGFBIp have increased aggregation propensity compared to the WT [21][22][23][24] . We have also previously reported the protein composition of the amyloid fibrils from Lattice Corneal Dystrophy patients (LCD) using mass spectrometric assays 25 . The proteolytic fragments of TGFBIp derived from amyloid fibrils of patients, upon digestion with trypsin showed a higher abundance of peptides from the 4 th FAS-1 domain of TGFBIp compared to healthy controls.…”
mentioning
confidence: 99%